VRAM flap for locally advanced breast cancer - Vieira, René Aloisio da Costa; Haikel, Raphael Luiz; Branquinho, Luciano Ipólito; Oliveira-Junior, Idam de (Mastology, 2021)
The authors presented a case of a patient with locally advanced breast cancer, with mammary and axillary localization, initially considered non-resectable, with good response after neoadjuvant chemotherapy. Due to the location of the lesion and the need for extensive resection, radical mastectomy was performed, associated with reconstruction with myocutaneous flap of the vertical rectus abdominis muscle. Different therapeutic options, the reasons that determine this choice, and local long-term control were discussed.